2015
DOI: 10.1117/1.jbo.20.5.056002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation ofin vivovital-dye fluorescence endoscopic imaging for the detection of Barrett’s-associated neoplasia

Abstract: Abstract. Current imaging tools are associated with inconsistent sensitivity and specificity for detection of Barrett's-associated neoplasia. Optical imaging has shown promise in improving the classification of neoplasia in vivo. The goal of this pilot study was to evaluate whether in vivo vital dye fluorescence imaging (VFI) has the potential to improve the accuracy of early-detection of Barrett's-associated neoplasia. In vivo endoscopic VFI images were collected from 65 sites in 14 patients with confirmed Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It has also been shown that texture features can be used to extract important spatial information about glandular architecture. 21 25 Since the colon mucosa images show quasiperiodic 2-D luminal patterns and texture features, frequency analysis was performance in the Fourier frequency domain. A power spectrum was calculated after a 2-D Fourier transform and evenly divided into 10 partitions using a previously reported method.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that texture features can be used to extract important spatial information about glandular architecture. 21 25 Since the colon mucosa images show quasiperiodic 2-D luminal patterns and texture features, frequency analysis was performance in the Fourier frequency domain. A power spectrum was calculated after a 2-D Fourier transform and evenly divided into 10 partitions using a previously reported method.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, thoracoscopy incorporating advanced nearinfrared (NIR) fluorescence imaging technologies has the potential to provide highly sensitive and specific imaging guidance of surgically interested regions. [10][11][12] Different from the color imaging, NIR fluorescence imaging only illuminates certain regions inside the field-of-view (FoV) and provides pathological information several millimeters beneath the tissue surface, which results in many advantages in the intraoperative usage. 13 Some recent preclinical and clinical applications already proved the feasibility and benefits of NIR image-guided MIS, such as its application in colorectal surgery, [14][15][16][17] bladder cancer, 18,19 cholecystectomy, 20 liver cancer, 21 and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%